Large-Scale Structural Variation Detection in Subterranean Clover Subtypes Using Optical Mapping - Yuan, Yuxuan; Milec, Zbyněk; Bayer, Philipp E.; Vrána, Jan; Doležel, Jaroslav; Edwards, David; Erskine, William; Kaur, Parwinder (Frontiers in Plant Science, 2018)
We selected two genetically diverse subspecies of the Trifolium model species, subterranean clover cvs. Daliak and Yarloop. The SVs discovered by Bionano optical mapping (BOM) were validated using Illumina short reads. In the analysis, BOM identified 12 large-scale regions containing deletions and 19 regions containing insertions in Yarloop. The 12 large-scale regions contained 71 small deletions when validated by Illumina short reads. The results suggest that BOM could detect the total size of deletions and insertions, but it could not precisely report the location and actual quantity of SVs in the genome. Nucleotide-level validation is crucial to confirm and characterize SVs reported by optical mapping. The accuracy of SV detection by BOM is highly dependent on the quality of reference genomes and the density of selected nickases.